Penggunaan Meme Sebagai Instrumen Penyebaran Informasi di Media Sosial Instagram - Wisnusyah, Muhammad; Muhaemin, Enjang; Ma'arif, Abdul Aziz (Annaba: Jurnal Ilmu Jurnalistik, 2020)
Activities on social media give rise to new cultural products, namely memes. The purpose of this research is to find out the elements, structure, and components contained in memes on the internet. The research uses a qualitative approach by using the content analysis method. The researcher used the Holsti model content analysis method, which is a research technique to draw conclusions by identifying the characteristics of the content of the message carried out systematically and objectively. The theory is used to dissect memes related to the April 11, 2022 demonstration circulating on Instagram. The results of the study found that, the elements contained in the demo action meme consist of three elements, namely text, image, and context that support each other. The structure used is three, namely image macros, snowclones, and exploitable images. The components contained in the demo action memes are a manifestation of the reality that really happened. Meme habits are used as a medium for conveying messages, meme ideals are shown as a form of disappointment, hope, and jokes.